Architectural project management success : a comparative case study between Yemen and Malaysia / Mohammed Hatim Mohammed Al-Sabahi - Al-Sabahi, Mohammed Hatim Mohammed (2014)
Although most project management experts agree that successful project management must involve control of quality, cost, and time, the management of architectural projects in Yemen remains inadequate. Therefore, Yemeni professionals must change their method of managing architectural projects to help conserve time, money, and natural resources. Most Yemeni architectural projects are implemented with inadequate and expensive design and construction practices, which led to low-quality buildings. The shortage of any approved national codes or standards only aggravates the construction industry's problems. This study aims to establish better methods to manage architectural projects in Yemen. The significant success criteria are evaluated, and the critical success factors required to ensure project success are identified. Architectural construction in Malaysia has astonished the world with its comprehensive growth and rapid development in the past decades. Yemen should learn and gain from the Malaysian approach, which should be a model for Yemen’s architectural construction. This research aims to compare the Yemeni and Malaysian approach in architectural project management. The objectives of this research are to explore process and project implementation, evaluate the criteria in determining time, cost, and quality, and identify success and failure factors of projects in Yemen and Malaysia. The primary objective is to provide guidelines for project implementation in Yemen, namely, the best practices in project management. Case study method and structured questionnaire survey method are applied in this research. Fieldwork involves the investigation of the stages of architectural projects in Yemen and Malaysia: from the design stage, the tender stage, and to the construction stage. Thematic narrative analysis is conducted to analyze the case studies. Data are examined with the statistical package for social sciences (SPSS). Percentages, frequency vi distribution, averages, and means are calculated and utilized as descriptive statistics. Cronbach’s alpha coefficient and Pearson correlation tests are employed for further data analysis. The results of the case study and survey in Yemen reveal that stakeholders involved in project implementation can develop the construction industry if they are subjected to strict regulations. The problem is not the lack of regulations but the failure of law enforcement officers to apply these regulations. The results of the case study and survey in Malaysia are different from those in Yemen in terms of professional attitude, commitment, innovation, and policies. Working time in Malaysia is respected as well as specialty; everyone has a specific job to do at a precise time. Qualification and technical education are found to be important in project implementation. Project success criteria, success factors, and failure factors are almost similar in both countries; however, their details differ significantly. Sixteen guideline points for project implementation in Yemen are provided.